The Interior Design of Juvenile Detention Class I in Kutoarjo, Central Java to Support the Rights of Child Prisoners - Ursula Devina; Andi Setiawan (Faculty Of Arts and Design Sebelas Maret University, 2023)
AbstractOne of the objectives of the Lembaga Pembinaan Khusus Anak (LPKA) is to provide guidance and rehabilitation for children involved in criminal offenses. Despite the efforts of Lembaga Pembinaan Khusus Anak (LPKA) to continuously improve its system, LPKA must ensure the fulfillment of children's rights in accordance with the principles stipulated in Law No. 11/2012. LPKA coaching that is less effective and not integrated with community life can be an indicator of the failure of child rehabilitation in LPKA. Therefore, there is a need for structured and integrated efforts to improve the effectiveness of rehabilitation of children in LPKA so that these children can return to being responsible and productive members of society. Prisoners who do not have access to adequate training or education may lack the necessary skills to find decent work and feel pressured to return to crime. The ideal LPKA interior should be able to provide access to facilities that are beneficial to juveniles. It is hoped that the idea of designing and planning the interior of the Class I Child Special Development Institution (LPKA) in Kutoarjo can be an evaluation material to see the field conditions about the actual facilities inside and the outside world. Especially to fulfill the rights of fostered children who must prepare for the future in social life.Keywords: Rights, Children, Recidivists, Rehabilitation